Stressors and its impact on work performance among military nurses in Metro Manila - Mangco, Carmen R. (1999)
The study of human behavior in organization focuses on establishing a "goodness of fit" between the worker and his environment. when humans interact with the environment, they are never completely free from stress. Stress is a universal part of life that affects billions of people in the workplace, in varying modes, intensity and duration. Nurses are not spared as they continue to confront life threathening and death situations in their line of work. Stress is more evident nowadays vis-a-vis the economic demands of daily living.Considered as a deterrent in the attainment of well-being and productivity, stress served as the focal of this study which sought to: identify the stressful factors confronting the military nurses; the strategies to offset these situations and the extent these stressors affect their performance.The conceptual framework of the study is derived from the fact that stress results from certain organizational and personal factors which interact either singly or in combination with one another that affect the physical, emotional and behavioral well-being of the military nurses in relation to their performance.This study made use of the descriptive survey correlational technique, which was conducted in four military hospitals based in Metro Manila. Utilizing the purposive sampling design, 134 military nurses served as participants of this study, the significant findings of which are as follows:1. The Nurse Corps as a technical service component of the Armed Forces of the Philippines stands out professionally in this male-dominated organization. The undergo rigid and progressive training in military institution to qualify for promotions and come up to set standards of performance, the focus of which is the efficiency and effective delivery of care.2. Military nurses undergo stressful experiences resulting from demands or external forces created by life changes, job responsibilities, family obligations and people. Also stress emanates from desires which are the internal forces, which include their expectations, goals and ambitions. Having no control of one's life of inability to fulfill these demands or desires can be stressful.3. A significant relationship exists between nurse's performance and variables such as values and commitment, orientation, structural aspects of the job and the kind of work environment. These imply that military nurses who perceive strong additional commitment to their work and to the organization manifest superior job performance.4. Perceived organizational and personal stressors encountered in their line of work point to the peculiar nature and demands of the job such as going on geographical assignments and the dilemma of having to strike a balance between military career and attendance to family obligations, as well as the fulfillment of individual needs and desires.5. Variables such as values and commitment, work environment, educational attainment, job demands and policies are significantly correlated with performance. The higher their perceptions to their contributions to mission accomplishment, the availability of administrative support, the acceptable workplace conditions in terms of supplies, equipment, level of safety, the stronger are their intentions to remain in the service for a longer time. A negative correlation existed between sex and performance, meaning, female military nurses, having nurtured inherently maternal and caring instincts are generally inclined to render better nursing care than their male counterparts. Perhaps it is because nursing is a mothering outpouring of care.
6. Positive coping strategies of the military nurses were manifested by acceptance of nature of job demands without further questions, strong support network provided by family and a high spirity of camaraderie existing among peers in the military organization. These were enough to contain the extent of stress to a moderate level (vm 3), as stress occurs two to three times during the work period.7. Moderate amoung of stress spur military nurses to improved work and better performance as evidenced by their very satisfactory Officer Evaluation Ratings, self-assessment of performance and inclusion in the latest promotional quota.8. Majority of nurses indicated that their loyalty and commitment to the Nurse Corps AFP serve as strong foundation to render continuous military service until their retirement.9. Among the variables that did not significantly relate the stress are:a. Logistics - the lack of equipment makes the staff improvise and get things done.b. Administrative support - although the superiors may be indifferent, this is compensated by the camaraderie and binding of colleagues.c. Domestic situation - perhaps this is a function of the support given by spouses and family members.10. The demographic variables that did not have significant relationship with stress are; age, rank, civil status, area of assignment, position, work schedule and life experiences. These variables did not cause or alter the presence of stress in the individual because they are as part of military nurse's life.Dealing with stress therefore is a mutual concern for the individual and for the employing organization. For the military nurses, it is significant because life, health, productivity and well-being can be at stake. For the military nursing service leaders, it is also important because over - all effectiveness will be affected when the military nurses do not perform at their level best. When this happens, the delivery of quality health caer to the AFP clientele will be compromised.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Stress; Nurses -- Job stress; Nurses -- Job performance